THE INFLUENCE OF THE PROBLEM SOLVING MODEL WITH SCIENTIFIC LITERACY ON STUDENTS' COMPETENCE ON GLOBAL WARMING MATERIAL AT SMP NEGERI 29 PADANG - Yaumil Khairiyah; Tuti Lestari (Department of Science Education, 2021)
Learning that is still teacher-centered makes students less active in solving problems and finds ideas in learning so as to make students' competencies low. With the low competency of business students, the business that can be done is by applying a problem solving model with scientific literacy. This model is in accordance with the demands of the 2013 curriculum which requires students to be active in learning. The purpose of this study is to describe the effect of the literacy problem solving model on the subject of Global Warming on the competence of students in SMP Negeri 29 Padang. This type of research is a Quasi Experiment with a randomized control group design posttest only design. The population is all eighth grade students of SMP Negeri 29 Padang in the academic year 2019/2020. The instrument used was a posttest question for knowledge competence, observation sheet for attitude competency and product assessment sheet for skills competency. For this research hypothesis was tested using t-test. The results of data analysis obtained are normally distributed and homogeneous data. It can be concluded that the hypothesis is accepted and there is a significant influence in the application of problem solving models with scientific literacy to students' competencies in global warming material at SMP Negeri 29 Padang.